The effectiveness of modified flip-based argumentation learning in improving students’ argumentation skills about hydrocarbon - Agustiningsih Agustiningsih; Ngatijo Ngatijo; Muhammad Haris Effendi-Hasibuan (Jurnal Pendidikan Kimia (JPKim), 2021)
The FBAL learning model is a learning model that has a specific purpose to improve students’ argumentation skills by integrating Toulmin's argumentation pattern. This study aimed to see the effectiveness of the Modified Flip-Based Argumentation Learning in improving students' argumentation skills about the concept of hydrocarbon compounds. The effectiveness was examined by comparing this model to Flip-Based Argumentation Learning and Flipped Classroom model. The factors that influence the differences in students’ argumentation skills amongst the three classes were also investigated. Concurrent embedded mix method design was used in this study. Some 93 students of 11 grade of SMA Negeri 1 Merangin Jambi were participated in this study. Data were collected using argumentation test (pre-test and post-test) and observations. The results showed that there was no difference between the Modified FBAL and FBAL in improving the students’ argumentation skills but both were different from the Flipped Classroom. The N-gain was 0.80 and 0.81 respectively for the Modified FBAL and FBAL. However, those were higher than the N-Gain of Flipped Classroom which was 0.71. Difference in providing the students with opportunities to practice their argumentation skills amongst the three models was the major factors influencing the students' argumentation skills in the three classes.  Keywords: argumentation skills, flip based argumentation learning, modified FBAL, flipped classroom, hydrocarbon compounds